The Stock Market and Investment - Barro, Robert J. (Review of Financial Studies, 1990)
Changes in stock prices have substantial explanatory power for U.S. investment, especially for long-term samples, and even in the presence of cash flow variables. The stock market dramatically outperforms a standard q-variable because the market-equity component of this variable is only a rough proxy for stock market value. Although the stock market did not predict accurately after the crash of October 1987, the errors were not statistically significant. Parallel relationships for Canada raise the puzzle that Canadian investment appears to react more to the U.S. stock market than to the Canadian market.